The effect of depression on occupational efficacy of higher vocational college students: the mediating role of psychological resilience and social support - Sun, Li; Zhang, Yeqing; Xie, Hongtao; Li, Qingwei; Zhu, Zhipei (Frontiers in Psychiatry, 2025)
ObjectiveTo understand the current situation of vocational college students’ mental health, take depression as independent variable, and explore the mechanism of social support and mental toughness as mediating variables on vocational college students’ career efficacy, so as to provide basis for effectively improving teenagers’ career efficacy, promoting teenagers’ mental health and future development.MethodsA total of 780 students in the first and second grades of high school in vocational schools were selected as the research objects by random cluster sampling. The questionnaire survey was conducted by the 9-item Patient Health Questionnaire (PHQ-9), Resilience Scale for Chinese Adolescents (RSCA), Social Support Rate Scale (SSRS) and career decision self-efficacy scale of secondary vocational students.ResultsDepression was negatively correlated with occupational efficacy, mental toughness and social support (P < 0.01). Psychological resilience was negatively correlated with occupational efficacy (P < 0.01), while social support was positively correlated with occupational efficacy (P < 0.01). The influence of mental toughness on occupational efficacy showed a masking effect, and the indirect effect accounted for 18.90% of the direct effect. Social support plays a partial mediating role in the effect of depression on occupational efficacy, accounting for 35.87% of the total effect.ConclusionPsychological resilience shows masking effect in the influence of depression on occupational efficacy, which is limited and influenced by personal cognition, and emphasizes the importance of emotional management. Social support plays an important role in reducing adolescent depression and improving adolescent occupational efficacy, and can effectively alleviate the adverse effects of depression on adolescent occupational efficacy. It is suggested that family, school and individual efforts should be made to strengthen the social support network, improve the psychological resilience of adolescents, and help improve their mental health level and professional efficacy.